Political Economy, Law And Expermientation - EN48 - 202301 - De Urioste Samanamud, Roberto Ricardo (2023)
Experimental Economics is a field that began with the proposition that economic theory can be testable in a controlled laboratory setting. Experimental work has been conducted in all fields of economics including Industrial Organization, Game Theory, Public Finance, General Equilibrium Theory and even Macroeconomics. Students will be introduced to the methods of experimental science, explore major subject areas that have been addressed through laboratory experiments, and learn of some of the major personalities at the intersection of economics, politics, and philosophy. Topics to be included reflect a variety of splits in the field: behavioral economics is more closely linked to psychology, neuroeconomics attempts to link behavior to specific areas of the brain, while the main branch, experimental economics, tries to learn about individual and group behavior given economic institutions and questions. This course also uses biographical or autobiographical readings to put the lessons learned in context history of political economic thought. Most importantly, this course has many carefully selected ¿hands-on¿ simulations of markets and interactions. These are used to reinforce a few key economic paradigms. Simulations are necessarily done in simplified environments in which the underlying economic theory or intuition is accessible to students with only a basic introductory economics background. Students who participate in the simulations learn from experience before seeing the relevant concepts from economics or politics. Participation by all stimulates discussion based on a common experience.